2008
DOI: 10.1002/maco.200804154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 08CH18N10T stainless steel corrosion in subcritical water by electrochemical noise analysis

Abstract: The corrosion behaviour of pressurized water reactor (PWR) steam generator tube material (08CH18N10T steel) was studied by electrochemical noise (EN) measurements and electrochemical impedance spectroscopy in high-temperature water at 280 8C and 8 MPa. Long-term measurements were performed in two electrolytes: (i) deionised water alkalized to pH 25 ¼ 9.5 by KOH; (ii) the same electrolyte with 200 ppm of chlorides added (as KCl). The noise data were processed by two filtering methods and the noise resistance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…3) can be used to provide quantitative impedance parameters in order to complement the qualitative analysis. In the last decade, such technique and particularly the proposed equivalent circuit have been intensively utilized by a number of researchers [11,15,19,[22][23][24][25][26][27][28][29][30][31].…”
Section: Equivalent Circuitmentioning
confidence: 99%
“…3) can be used to provide quantitative impedance parameters in order to complement the qualitative analysis. In the last decade, such technique and particularly the proposed equivalent circuit have been intensively utilized by a number of researchers [11,15,19,[22][23][24][25][26][27][28][29][30][31].…”
Section: Equivalent Circuitmentioning
confidence: 99%
“…The physical significance of the elements in the proposed equivalent circuit has been intensively reported in the literature 20–26, 30–38. In the proposed equivalent circuit, R el corresponds to the resistance of the electrolyte (0.5 M NaCl solution).…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al [121] found a linear relationship between the weight loss rate of 304SS in hightemperature water and the reciprocal of noise resistance, consistent with the research results in room-temperature systems. Macák et al studied the corrosion behavior of 304SS [122] and 08CH18N10T steel [123] in high-temperature water. They found that during the initial soaking stage, the noise resistance increased first and finally became stable.…”
Section: Electrochemical Noisementioning
confidence: 99%